The first Korean species of Euconnus (Cladoconnus), with a synopsis of the E. ussuriensis species group (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
Most species of Euconnus (Cladoconnus) inhabit West Palaearctic, and only three are known from East Asia. The latter form a morphologically uniform group that comprises E. ussuriensis (Primorsky Krai), E. matsuae (Central Honshu) and E. nakahamai (Shikoku). These species cannot be reliably distinguished by external features; they differ mainly in the shape of the endophallic sclerites. Diagnostic characters of these species are summarized, and a new member of the E. ussuriensis species group is described, Euconnus (Cladoconnus) rudimentalis n. sp. (South Korea). Members of this group are restricted to the areas surrounding the Sea of Japan; the known distribution suggests that similar species can be expected to occur also in the northern part of the Japanese Archipelago and in North Korea.